Dynamics of Religious Behavior of Street Vendors in Narmada Terminal, West Lombok Regency: An Anthropological-Phenomenological Study - Zaelani, Kamarudin; Mulianah, Baiq; Sakaroni, Rubiyatna (Islam Realitas: Journal of Islamic and Social Studies, 2024)
This study examines the dynamics of religious behavior among street vendors in the Narmada District, West Lombok Regency, West Nusa Tenggara Province. Religion is comprehensively understood to encompass both esoteric dimensions (belief, conviction, and spiritual experiences) and exoteric dimensions (rituals and practices). The study employs a religiosity research approach and an anthropological-phenomenological method. Out of 42 vendors, the research sample includes 10 street vendors selected through purposive sampling. Primary data is collected through in-depth interviews with street vendors and village authorities, while secondary data is gathered through observation and literature review to capture the phenomena and manifestations of religious behavior. This study found that the typology of religious behavior of street vendors in Narmada identified forms a unique pattern, characterized by conditional behaviors that mimic the priyayi style, adopt a santri-like demeanor at specific times, or embrace an abangan style. These behavioral patterns are influenced by internal factors, such as psychological conditions (hope and fear), and external factors, including pragmatic positivist elements (government policies, community dynamics, modernism, technology, and education levels). Economic conditions and the nature of the vendors' occupation also play a crucial role in shaping and attributing meaning to their religious behavior. Penelitian ini mengamati dan menguraikan dinamika perilaku keagamaan di kalangan pedagang kaki lima (PKL) di Terminal Narmada, Kabupaten Lombok Barat. Pemahaman agama didefinisikan secara menyeluruh, mencakup dimensi esoterik (keyakinan, kepercayaan, dan pengalaman spiritual) dan dimensi eksoterik (ritual dan praktik). Menggunakan pendekatan penelitian religiositas dan metode antropologis-fenomenologis, data primer diperoleh melalui wawancara mendalam dengan PKL dan aparat desa, sedangkan data sekunder diperoleh melalui observasi dan tinjauan pustaka untuk menangkap fenomena dan manifestasi perilaku keagamaan. Penelitian melibatkan 10 PKL yang dipilih melalui teknik purposive sampling. Tipologi perilaku keagamaan yang muncul membentuk pola unik, meliputi perilaku bersyarat yang menyerupai gaya priyayi, bersikap santri pada waktu tertentu, atau mengikuti gaya abangan. Faktor internal, seperti kondisi psikologis (harapan dan ketakutan), dan faktor eksternal, termasuk elemen positivis pragmatis (kebijakan pemerintah, dinamika masyarakat, modernisme, teknologi, dan tingkat pendidikan), memengaruhi pola-pola perilaku ini. Kondisi ekonomi dan jenis pekerjaan juga memainkan peran penting dalam membentuk dan memberikan makna pada perilaku keagamaan PKL di Terminal Narmada, Kabupaten Lombok Barat, NTB